2006
DOI: 10.1080/00379271.2006.10697476
|View full text |Cite
|
Sign up to set email alerts
|

Calyx fluid proteins of twoCotesia sesamiae(Cameron) (Hymenoptera: Braconidae) biotypes in Kenya: implications to biological control of the stem borerBusseola fusca(Fuller) (Lepidoptera: Noctuidae)

Abstract: Abstract. Cotesia sesamiae (Cameron) (Hymenoptera: Braconidae) is an indigenous larval endoparasitoid of Busseola fusca (Fuller) (Lepidoptera: Noctuidae) in sub-Saharan Africa. In Kenya, reports suggest that C. sesamiae occurs as two biotypes. Biotype avirulent to B. fusca gets encapsulated by haemocytes in this host and is unable to complete development. Biotype virulent to B. fusca is able to overcome immune defences. Factors present in the calyx fl uid such as the PolyDNAviruses (PDV), venom and calyx fl ui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…In Kenya, C. sesamiae exists as two biotypes that differ in their ability to parasitize B. fusca . Cotesia sesamiae from western Kenya completes development in B. fusca larvae, hence it is virulent (Gitau et al. 2006), while in the coastal C. sesamiae biotype the eggs that are oviposited are encapsulated by haemocytes in B. fusca larvae, and hence it is avirulent.…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya, C. sesamiae exists as two biotypes that differ in their ability to parasitize B. fusca . Cotesia sesamiae from western Kenya completes development in B. fusca larvae, hence it is virulent (Gitau et al. 2006), while in the coastal C. sesamiae biotype the eggs that are oviposited are encapsulated by haemocytes in B. fusca larvae, and hence it is avirulent.…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya, C. sesamiae exists as two biotypes that differ in their ability to parasitise B. fusca. Cotesia sesamiae from western Kenya completes development in B. fusca larvae, while in the coastal C. sesamiae biotype the eggs that are oviposited are encapsulated by haemocytes in B. fusca larvae (Gitau, Dupas, Ngi-Song, Mbugi, and Schulthess 2006). It was suggested that this is due to differences in polyDNA viruses (PDV) (Dupas, Gitau, and Silvain 2006;Gitau et al 2006) that are injected together with the egg at oviposition.…”
Section: Reproductive Compatibility Of Several East and West African mentioning
confidence: 97%
“…Cotesia sesamiae from western Kenya completes development in B. fusca larvae, while in the coastal C. sesamiae biotype the eggs that are oviposited are encapsulated by haemocytes in B. fusca larvae (Gitau, Dupas, Ngi-Song, Mbugi, and Schulthess 2006). It was suggested that this is due to differences in polyDNA viruses (PDV) (Dupas, Gitau, and Silvain 2006;Gitau et al 2006) that are injected together with the egg at oviposition. The PDV genes are expressed in the host larvae, causing the destruction of haemocytes, thus preventing encapsulation of the eggs (Beckage and Gelman 2004).…”
Section: Reproductive Compatibility Of Several East and West African mentioning
confidence: 97%
“…An important measure of both host resistance and parasitoid virulence is the ability of a host to kill parasitoid eggs or larvae via mechanisms such as encapsulation. In a given species, this ability may vary geographically [ 4 , 5 ] and depend on a degree of specialization [ 6 , 7 ]. It varies as a response to stress [ 8 , 9 ] and in association with endosymbionts [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%